EFEKTIVITAS PELAKSANAAN BEUT AL-QURAN BA’DA MAGHRIB DI KABUPATEN ACEH BESAR - Azwir Azwir (Jurnal Ilmiah Didaktika, 2017)
Learning the Quran is regarded as an essential activity in Muslim world in order to educate their young generations. However, in Aceh Besar district, many children and teenagers are not accustomed to reciting the Quran after the sunset prayer, but instead wandering around the street. Therefore, in 2012, the local government initiated a program of Beut al-Quran Ba’da Magrib in all villages in Aceh Besar district. This study attempted to figure out the effectiveness of the implementation of the program, strategy used, and impacts on the people in Aceh Besar. Held in Aceh Besar district, the study used cluster-based purposive sampling in Banda Safa, Lamcot, and Meunasah Karieng Lamlhom villages. The research participants were the Head of Islamic Law Office of Aceh Besar, teungku (Islamic teachers) of the program, santri (students) of the program, and community figures. In addition, the researcher had also collected some important documents reagrading this program. The data were collected by interview, observation, and documentation. The data were also triangulated. The findings indicated that the implementation of Beut al-Quran Ba’da Magrib program was not effective as expected. The strategy used was requiring school aged children to take part in the program. The impacts, however, were very good as the program has induced positive spirit of the young learners, as well as of the community and local environment. The positive impacts have encouraged other villages to implement similar programs. Nevertheless, there were still some obstacles that need to attention during the implementation of the program.